TYPE OF LEADERSHIPS, ACCOUNTABILITY, PUBLIC PARTICIPATION AND TRANSPARENCY OF PUBLIC POLICY AS MODERATION TO DEGREE OF LEGISLATIVE’S MEMBERS BUDGETING KNOWLEDGE IN CONTROLLING THE REGIONAL BUDGET (APBD) - Aprianto L. Kuddy (Universitas Cenderawasih, 2016)
The purpose of this research was to examine the influence of the quality of board of the council knowledge about budget and the control board of the council on Regional Budget (APBD) with leadership types, accountability, participation and public policy transparency as the moderating variables that strengthen or weaken the relationship. Independent variable of this research is quality of board of the council knowledge about budget and the control board of the council on Regional Budget (APBD) as a dependent variable. The analysis of this research was a member of the board council at Regional Representative Council (DPRD) of Papua Province, Regional Representative Council (DPRD) of Jayapura Regency and Regional Representative Council (DPRD) of Jayapura Municipality for the period of 2009 to 2014. The number of respondent of this research was 111 respondents. The data was obtained by direct surveys and the hypothesis was tested with multiple regressions analysis. The result showed that board of the council’s knowledge about budget influenced the control board on Regional Budget (APBD). Besides, this research also documented that interaction between leadership type with knowledge about budget and interaction between public participation with knowledge about budget influenced the control from board on the Regional Budget (APBD). On the other hand, both interaction between accountability and public policy transparency did not influence the control board of the council on Regional Budget (APBD). Keywords : Leadership type, Accountability, Public participation, Transparency in Public Policy, Budgeting knowledge, Control board on Regional Budget (APBD).